FROM BROWSING TO BUYING: MICRO-CELEBRITY CONTENT AUTHENTICITY AND GEN Z’S IMPULSE PURCHASING BEHAVIOR - Lady Lady; Kelly Lim; Hepy Hefri Ariyanto (Jurnal Ilmiah Akuntansi, Manajemen dan Ekonomi Islam (JAM-EKIS), 2026)
The rapid acceleration of digital transformation has significantly reshaped consumer patterns, particularly among Generation Z, who increasingly rely on online marketplaces for skincare consumption. Grounded in the Stimulus–Organism–Response (S–O–R) framework, this study analyzes how micro-celebrity content authenticity influences utilitarian and hedonic browsing, and how these internal processes subsequently drive reminiscence and designed impulse purchases. Utilizing a quantitative approach, data were collected from 266 valid Generation Z respondents in Indonesia through purposive sampling and analyzed using Partial Least Squares Structural Equation Modeling (PLS-SEM). The results support all seven hypotheses, indicating that micro-celebrity content authenticity acts as a significant stimulus triggering both rational and emotional search patterns. Notably, hedonic browsing was identified as the critical mediating mechanism translating authentic digital content into spontaneous buying actions, exerting the strongest influence on reminiscence impulse purchases. These findings enrich the theoretical understanding of online consumer behavior and provide practical insights for skincare brands to prioritize content credibility and emotional engagement over traditional advertising metrics